COMMUNICATION STRATEGY POPULATION AND CIVIL REGISTRY IN SOCIALIZING CHILD IDENTITY CARD IN DISTRICT BANGKINANG KOTA IN KAMPAR DISTRICT - Annisa Novita; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Child Identity Card (KIA) is a card issued by the government to collect data, provide protection, and fulfill the constitutional rights of children in Indonesia. Besides will be a valid identification or proof of self to the child, especially will make children can do public service independently, and meet their needs easily, quickly and cheap, such as education, health, and other social activities. Kampar regency being one of the current Child Identity Card program implementers is based on the largest number of birth certificates in the region.The purpose of this research is to know how communicator strategy, audience strategy, message planning and media selection of Department of Population and Civil Registry in socializing Child Identity Card program. This research uses qualitative research method with descriptive analysis. The informant of this research is five people chosen purposively. Data collection techniques used are observation, interview, and documentation. Data validity technique used in this research is triangulation and extension of participation. The results obtained show that the strategy communicator conducted by the Department of Population and Civil Registry of Kampar Regency is by first determining the target communicator, determining how to communicate and credibilita ssumber who have the readiness and seriousness in disseminating the Child Identity Card to the community. Then the target audience is divided into 3 segments. Schools, hospitals / clinics, and the general public. Message planning is used directly to the message, through two format of organizing message that is topical format, spatial format and problem solving which then maximize delivery of message with actual message style. The last use of media is done by using mass media which is divided in electronic media and print media so that can reach all layers of society. Keywords: Communication Strategy, Socializing, Child Identity Card